Clinical Profile, Indications and Findings of Emergency Exploratory Laparotomies in a Teaching Hospital in Nigeria: A Retrospective Review for Policy and Practice - Inegbenosun Iluobe; Osayomwanbo Osaheni (International Journal of Medical Science and Clinical Research Studies, 2026)
Background: Emergency exploratory laparotomy entails abdominal procedure done for the purpose of making diagnosis of an acute intraabdominal condition requiring immediate surgical intervention. The procedure is associated with significant morbidity and mortality, particularly in developing countries like ours, due to its emergent nature, delayed presentation, and limited time for perioperative correction of deranged parameters and optimization of patients before surgery. Knowledge of clinical profile, indications and intra-operative findings is crucial for improving perioperative care and patient survival, especially in teaching hospitals where these very sick patients presents to. The study aimed to highlight the clinical profile, indications and findings of emergency exploratory laparotomies in a teaching hospital in Nigeria. Method: This three-year tertiary hospital-based observational study of emergency exploratory laparotomies performed at the University of Benin Teaching Hospital (UBTH), Nigeria from 2023-2025. A total of 104 patients presenting with acute abdominal conditions requiring emergency surgical intervention were recruited in the study. Data were obtained from patients' hospital record included patients' demographic characteristics, clinical presentations, indications and intraoperative findings. Results: A total of 104 patients underwent emergency exploratory laparotomy with male preponderance of 60.6%. The most common age group who had emergency exploratory laparotomy were